Sistem Diagnosa Laying Hens Disease menggunakan Dempster Shafer - Andika Nanda Manurung; Muhammad Ardiansyah Sembiring; Wiwin Handoko (Universitas Hamzanwadi, 2023)
Laying hens are animals that are widely bred by people in Indonesia, especially in the province of North Sumatra as a form of micro, and medium enterprises, commonly abbreviated as UMKM. In order to improve health and avoid disease in these animals, it is necessary to have the knowledge to deal with the symptoms of existing diseases. The purpose of this study is to create a system for diagnosing disease in laying hens using the Dempster Shafer method. The stages of making this system are analysis, design, implementation, and testing. Collecting data on the study through observation and interviews about diseases in these animals. Meanwhile, in this research design, application architecture and interfaces are created. Data analysis technique using Dempster Shafer and testing is done shade Blackbox. Our findings are an expert system that can diagnose dempster shader hens’ disease. This system can also be implemented using the Dempster Shafer method and is then running well and can provide diagnosis results with an accuracy of 99.04%. In addition, the test results show that the modules in this system are already functioning and successfully based on the Blackbox results. Therefore, this system can be used to find out the symptoms of disease in laying hens, especially in the Food Security and Animal Husbandry Service of North Sumatra Province, which is Asahan Regency.